2024
DOI: 10.1038/s41467-024-45702-4
|View full text |Cite
|
Sign up to set email alerts
|

High-spin Co3+ in cobalt oxyhydroxide for efficient water oxidation

Xin Zhang,
Haoyin Zhong,
Qi Zhang
et al.

Abstract: Cobalt oxyhydroxide (CoOOH) is a promising catalytic material for oxygen evolution reaction (OER). In the traditional CoOOH structure, Co3+ exhibits a low-spin state configuration ($${t}_{2{{{{{\rm{g}}}}}}}^{6}{e}_{{{{{{\rm{g}}}}}}}^{0}$$ t 2 g 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As the Fe doping content increases, the Co 2p of CN/Fe-CoS 2 -0.2 appears as a new diffraction peak corresponding to Co 3+ at 778.8 and 793.5 eV, and Fe doping is facilitated to move Co 2+ to Co 3+ . Co 3+ has been reported to be the active site for the large H 2 O molecule adsorption energy and low coordination number, leading to high-efficiency catalytic activity. , Upon a further increase in the Fe doping level, the promotional effect of Fe on the conversion of Co 2+ to Co 3+ reaches a critical point. The Co 2p spectrum of CN/Fe-CoS 2 -0.3 exhibits a similarity to that of CN/Fe-CoS 2 -0.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Fe doping content increases, the Co 2p of CN/Fe-CoS 2 -0.2 appears as a new diffraction peak corresponding to Co 3+ at 778.8 and 793.5 eV, and Fe doping is facilitated to move Co 2+ to Co 3+ . Co 3+ has been reported to be the active site for the large H 2 O molecule adsorption energy and low coordination number, leading to high-efficiency catalytic activity. , Upon a further increase in the Fe doping level, the promotional effect of Fe on the conversion of Co 2+ to Co 3+ reaches a critical point. The Co 2p spectrum of CN/Fe-CoS 2 -0.3 exhibits a similarity to that of CN/Fe-CoS 2 -0.2.…”
Section: Resultsmentioning
confidence: 99%
“…50 Co 3+ has been reported to be the active site for the large H 2 O molecule adsorption energy and low coordination number, leading to high-efficiency catalytic activity. 51,52 Upon a further increase in the Fe doping level, the promotional effect of Fe on the conversion of Co 2+ to Co 3+ reaches a critical point. The Co 2p spectrum of CN/Fe-CoS 2 -0.3 exhibits a similarity to that of CN/Fe-CoS 2 -0.2.…”
Section: Synthesis Of Fe-zif-67mentioning
confidence: 99%
“…When the energy of the anti-bonding orbital is higher than that of the Fermi level, the degree of occupation is lower, the adsorption strength is higher, and the spin polarization is higher. 71…”
Section: Fundamentalsmentioning
confidence: 99%
“…58,75,76 Moreover, the electron transfer rate that occurs in the top-to-top orbital is higher than that in the face-to-face orbital. 77 Hence, Xue et al 71 reported that, compared with the low spin state with the orbital near the Fermi level, the high spin state with the orbital near the Fermi level has a faster electron transfer rate. Thus, the spin transition would impact the rate of electron transfer and regulate the catalytic reaction dynamics (Fig.…”
Section: Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation